Clinicopathological Characteristics of Young-Onset Breast Cancer Patients Stratified by Molecular Subtypes at H. Adam Malik Hospital - Raka Dutra Pratama; Dedy Hermansyah; Pimpin Utama Pohan (Medicinski glasnik, 2025)
Aim: To examine and evaluate the clinicopathological characteristics of young-onset breast cancer across molecular subtypes in patients from Southeast Asia, with a specific focus on those treated at H. Adam Malik Hospital, Indonesia. Methods: A descriptive observational study with a cross-sectional design was conducted on medical records of breast cancer patients aged <40 years treated at H. Adam Malik Hospital from January 2017 to December 2022. Data included demographic, clinical, histopathological, and immunohistochemical findings. Statistical analyses were performed descriptively. Results: Among the 104 patients analyzed, 71 (69.2%) had T4 tumors, and 49 (47.1%) had NST-type tumors. Most cases lacked ER (72, 69.2%) and PR (71, 68.3%) expression. A total of 41 patients had poorly differentiated tumors, with the majority at stage IV. The HER-2 positive subtype was most common (39, 37.5%), followed by Luminal B (31, 29.8%) and TNBC (22, 21.2%). Conclusion: Young-onset breast cancer at H. Adam Malik Hospital predominantly features advanced stages, aggressive histopathological grades, and a high prevalence of HER2-positive and Luminal B subtypes. These findings highlight the importance of early detection and personalized treatment approaches.
Keywords: molecular subtypes; cross-sectional studies; Breast Cancer; young adult; medical records